Pengembangan Media Video Edukasi tentang Pengetahuan Pemilihan Snack pada Remaja - Putri, Qori' Selviana; Rakhma, Luluk Ria (Poltekkes Kemenkes Jambi, 2024)
Background: Adolescents aged 13-18 years experience rapid growth, leading to increased nutritional needs. This age group often seeks additional snacks outside of meal times due to heightened appetite. However, not all snacks are nutritious. Another issue is the low food safety level of snacks sold freely in school canteens and the surrounding environment, which may not meet adolescents’ nutritional needs. This study aims to develop, determine the suitability, and assess the acceptability of video-based nutrition education media about adolescent snack selection. Method: This research utilized the Research and Development (R&D) method, encompassing analysis, design, development, implementation, and evaluation stages. The subjects included material experts, media experts, and target audience acceptability tests. The research object was video media. Results: The media suitability test by material experts averaged 4.37, with a CVI of 1.00. Media experts rated it at 4.47 with a CVI of 0.96. The acceptability test scored an average of 4.5 with a CVI of 1.00. Conclusion: The video media is highly suitable and highly suitable for use as an information tool to increase knowledge about snack selection among adolescents. Keywords: Adolescents; Snacks; Video Media.